Pembuatan asesmen autentik model pembelajaran learning cycle 5E materi momentum, impuls dan gerak harmonik sederhana untuk SMA - Sani Aprisilia; Festiyed Festiyed; Hamdi Hamdi; Wahyuni Satria Dewi (Universitas Negeri Padang, 2019)
The application of learning in the classroom cannot be separated from learning model and tools needed in learning. Among the model and needs are learning cycle 5E and assessment. This is the research that is focused on making authentic assessment for Learning Cycle 5E model with measured validity value. The mater that chosen are momentum, impulse and simple harmonic motion. In this research, an authentic assessment worksheet product was made. Making an authentic assessment is done by following the step of authentic assessment making by O’Malley. Whereas for the manufacture of the authentic assessment worksheet product done by using step provided in the instruction of development of teaching textbook by the Ministry of National Education (2008). To determine the value of product validity, a validation process was carried out twice. First validation shows the validity value as 80,12 means it is stated the product is valid. The increase in value of product validity is seen in the second validation which the score is 86,57 that is can be concluded as the authentic assessment was made are very valid.